Perlindungan dan Penegakan Hukum Terhadap Korban Kejahatan Seksual dan Pemerasan di Aplikasi Pertemanan Online - Grenaldi, Laurensius (Jurnal Ilmiah Wahana Pendidikan, 2024)
Rapid advancements in internet network technology are necessary in light of the severe restrictions placed on various community activities by the global Covid-19 epidemic. The prevalence of sexual violence against minors and adolescents on dating apps is also influenced by the disorder. It is insufficient to address issues under Law No. 44 of 2008 on pornography (also known as the Pornography Act) and/or Law No. 11 of 2008 on information and electronic transactions as amended by Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Information and Electronic Transactions (also known as the ITE Act). Finding a legislative framework and protections that would better assist victims of sex crimes and extortion via dating apps was the study's goal. This article employs doctrinal (dogmatic) legal research methods. In an effort to broaden awareness of criminal law, the strategy looks at law enforcement protocols as well as legal safeguards for victims of sex crimes and extortion via online dating apps. The results of this study show that victims have not obtained justice and that different branches of Indonesian law enforcement still do not have a victim-centered perspective when it comes to regulation and victim protection. It even demonstrates how some aspects of current laws might be exploited to undermine moral principles. However, there are still legal issues associated with the misuse of technologies like cybersex that might have elements of decency.